2016
DOI: 10.4314/ijbcs.v10i3.19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in vitro de l’activité des écorces de tige de Anogeissus leiocarpus (DC) Guill. et Perr. (Combretaceae) sur des bactéries responsables de maladies courantes en Afrique et criblage phytochimique

Abstract: Evaluation in vitro de l'activité des écorces de tige de Anogeissus leiocarpus (DC) Guill. et Perr. (Combretaceae) sur des bactéries responsables de maladies courantes en Afrique et criblage phytochimique ; Tel : (225) 08687153 RESUME Les bactéries sont à l'origine de réel problème de santé publique à cause de leur implication dans de nombreuses maladies. Leur résistance aux antibiotiques est devenue l'un des problèmes les plus importants dans la lutte contre les maladies infectieuses dans le monde. L'objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
4
3
1
1
Order By: Relevance
“…The phytochemical study of the ethanolic extract of Anogeissus leiocarpus stem bark revealed the presence of alkaloids, tannins, flavonoids, anthocyanins, sterols and terpenoids, and saponosides. These results corroborate with those of Sanogo et al in 2016 [11] in Côte d'Ivoire who obtained alkaloids, tannins, flavonoids, anthocyanins, sterols and terpenoids, saponosides, but our results was differ from those obtained by Mann et al in 2008 [12] in Nigeria who noted the absence of tannins in the stem bark of Anogeissus leiocarpus; and that could be explain by the difference in the harvesting period and edaphic factors [24] . The free radical scavenging activity of the ethanolic extract of Anogeissus leiocarpus, revealed by the DPPH colorimetric method, is due to the presence of flavonoids in Anogeissus leiocarpus extracts.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The phytochemical study of the ethanolic extract of Anogeissus leiocarpus stem bark revealed the presence of alkaloids, tannins, flavonoids, anthocyanins, sterols and terpenoids, and saponosides. These results corroborate with those of Sanogo et al in 2016 [11] in Côte d'Ivoire who obtained alkaloids, tannins, flavonoids, anthocyanins, sterols and terpenoids, saponosides, but our results was differ from those obtained by Mann et al in 2008 [12] in Nigeria who noted the absence of tannins in the stem bark of Anogeissus leiocarpus; and that could be explain by the difference in the harvesting period and edaphic factors [24] . The free radical scavenging activity of the ethanolic extract of Anogeissus leiocarpus, revealed by the DPPH colorimetric method, is due to the presence of flavonoids in Anogeissus leiocarpus extracts.…”
Section: Discussionsupporting
confidence: 87%
“…According to the World Health Organisation (WHO), 80% of the African population uses traditional medicine to meet their health care needs [9,10] . Indeed, Anogeissus leiocarpus was indicated in the treatment of certain diseases such as urinary bilharzia, amoebic dysentery, malaria, burns, pain, trypanosomiasis, helminthiasis, anorexia, constipation, fatigue, eczema, psoriasis, and diarrhea [11,12,13] . Thus, to valorize the medicinal plants of the Chadian pharmacopoeia, particularly Anogeissus leiocarpus (DC) Guill and Perr traditionally used in the treatment of microbial affections, this study was carried out to evaluate their antiradical and antibacterial activities with a view to formulating traditionally improved phyto medicines.…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical screening permitted to identify tannins, flavonoids, leuko-anthocyanins, saponosides, coumarins, anthocyanins, heterosides (O and C), reducing compounds and free anthracenics in A. leiocarpus leaf powder. Only eight groups of chemical compounds were identified in the bark powder of the same species including tannins, flavonoids, alkaloids, terpenes and saponosides [22]. The type of organs used could explain these results [15], however, did not find the coumarins, free anthracenics and glycosides in ethanolic extracts of A. leiocarpus leaves but contrary to this study, they found quinonic derivatives in those extracts.…”
Section: Phytochemical Screeningcontrasting
confidence: 86%
“…The phytochemical studies led to the identification of several families of chemical compounds in the two plant leaves. Several chemical constituents of plants were precursors of the pharmacological effects [22]. Overall, the phytochemicals found varied from plant to plant with a complete absence of cyanogenic derivatives in both plants.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…En effet, une valeur de CIM de 500 µg/ml avait été obtenue pour un extrait éthanolique d'écorce de tige vis-à-vis de C. albicans (Kubmarawa et al, 2007). Les extraits méthanoliques 70% et aqueux des écorces de tige de A. leiocarpa ont eu un effet bactéricide sur 100% des souches bactériennes testées par Sanogo et al (2016). Diatta et al (2019) ont montré que l'extrait aqueux de bâtonnets frotte-dents de tiges de S. birrea est d'une richesse phytochimique intéressante avec des composés de classes variées (stéroïdes, tanins, saponines, anthocyanines, coumarines, émodines).…”
Section: Discussionunclassified